2003
DOI: 10.1023/b:ejep.0000027351.18118.7c
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Information Experience of Women Invited for Cervical Screening for the First Time in 1994 with 2001

Abstract: We compared the information experience of women invited to attend cervical screening for the first time in 1994 and 2001 using postal questionnaires. Compared to 1994, women in 2001: found the invitation letter less easy to understand; were not aware of alternative venues for the test; and waited >4 weeks before receiving their results. Negative information experiences may influence attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In our study, patient compliance was the single greatest contributing factor to the development of cervical cancer, being identified as the principle factor in 45% of cases and a contributing factor in a further 11.4%. Factors associated with non‐compliance with cervical screening are well recognised, in particular anxiety and embarrassment, 19 and it appears that the level of knowledge and understanding of women is not improving with time 20 . Many strategies have been employed to overcome the obstacle of compliance at the screening and referral level, including reminder letters and phone calls, detailed information leaflets and pre‐colposcopy discussion sessions 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patient compliance was the single greatest contributing factor to the development of cervical cancer, being identified as the principle factor in 45% of cases and a contributing factor in a further 11.4%. Factors associated with non‐compliance with cervical screening are well recognised, in particular anxiety and embarrassment, 19 and it appears that the level of knowledge and understanding of women is not improving with time 20 . Many strategies have been employed to overcome the obstacle of compliance at the screening and referral level, including reminder letters and phone calls, detailed information leaflets and pre‐colposcopy discussion sessions 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in local result notification strategies have previously been described11 17 23 despite the existence since 1997 of national screening guidelines for the provision of written information 24. Variable result communication is not unique to the UK setting 6 8 2527.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the routine delivery of result information across the NHSCSP, although some have described methods by which specific groups of women in different areas are informed of results 11 17. A questionnaire survey of general practices within a single health authority (Nottingham) showed that the method and content of communications imparting mild or borderline screening test results varied widely 11.…”
mentioning
confidence: 99%
See 1 more Smart Citation